2012
DOI: 10.2139/ssrn.2198836
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Assertiveness Level of College Students Who are Doing Orienteering Sports

Abstract: In essence, Assertiveness is an inclination to undertake new and daring enterprises. Namely, it's the trait of being adventurous. Assertiveness is an important aspect of communication with others, and it's also a decisive factor of getting engage with people. In this study, it's aimed to study Assertiveness level of college students who is doing Orienteering Sports in terms of some variables. This study is carried out will a survey of 7 questions regarding students' personal information and Rathus' Assertivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…In another study conducted by Crassini et al (2007) revealed that women reported to be more assertive than men on some items. However, in few studies men are more assertive than women (Coşkuner et al, 2013;Kimble et al, 1984). The hypothesis of this study stating that there will be no significant difference in the levels of Assertiveness between men and women has been accepted.…”
Section: Resultsmentioning
confidence: 76%
“…In another study conducted by Crassini et al (2007) revealed that women reported to be more assertive than men on some items. However, in few studies men are more assertive than women (Coşkuner et al, 2013;Kimble et al, 1984). The hypothesis of this study stating that there will be no significant difference in the levels of Assertiveness between men and women has been accepted.…”
Section: Resultsmentioning
confidence: 76%
“…Since this was the first study of this kind in the sports community, there is an urgent need for its repetition in other samples to obtain results for empirical comparisons and confirmations. According to the results of other studies on the effect of age, gender, and skill level on assertiveness [36], it is suggested that studies be conducted on samples with a different age range and in different societies to generalize and compare the results. It is also suggested that future studies be more extensive with long-term follow-ups to determine the effect of assertiveness training after a longer period.…”
Section: Resultsmentioning
confidence: 99%